A network slacks-based measure considering dual-role factors and undesirable outputs for assessing the efficiency of supply chains - Chongyu Ma; Jianwei Ren; Chunhua Chen (Scientific Reports)
Abstract In the production of supply chains, dual-role factors and undesirable outputs are commonly encountered. However, current research fails to effectively address these factors, leading to inaccurate assessments of efficiency. To address these limitations, this study proposes a method called the network slacks-based measure considering both dual-role factors and undesirable outputs. Our methodology treats dual-role factors as strongly disposable and employs 0–1 programming to manage these factors, while utilizing the slacks-based approach to handle undesirable outputs. Data from 10 automotive supply chains are collected to validate the effectiveness of the proposed method. To examine the impact of intermediate products, we compare their efficiency under different link activities. The findings suggest that using fixed links to manage intermediate products may overestimate production efficiency. Furthermore, the impact of dual-role factors is evaluated under two scenarios: weak disposability and the exclusion of dual-role factors. The results demonstrate that treating dual-role factors as weakly disposable may overestimate efficiency, whereas ignoring them may lead to an underestimation of efficiency.